Prospective observational cohort study on epidemiology, treatment and outcome of patients with traumatic brain injury (TBI) in German BG hospitals. Issue 6 (4th June 2021) - Schwenkreis, Peter; Gonschorek, Andreas; Berg, Florian; Meier, Ullrich; Rogge, Witold; Schmehl, Ingo; Kern, Bodo Christian; Meisel, Hans-Jörg; Wohlfarth, Kai; Gross, Stefan; Sczesny-Kaiser, Matthias; Tegenthoff, Martin; et al.
Abstract : Objectives: Since 2000/2001, no large-scale prospective studies addressing traumatic brain injury (TBI) epidemiology in Germany have been published. Our aim was to look for a possible shift in TBI epidemiology described in other European countries, to look for possible changes in TBI management and to identify predictors of 1-year outcome especially in patients with mild TBI. Design: Observational cohort study. Setting: All patients suffering from a TBI of any degree between 1 October 2014 and 30 September 2015, and who arrived in one of the seven participating BG hospitals within 24 hours after trauma, were included. Participants: In total, 3514 patients were included. Outcome measures: Initial care, acute hospital care and rehabilitation were documented using standardised documentation forms. A standardised telephone interview was conducted 3 and 12 months after TBI in order to obtain information on outcome. Results: Peaks were identified in males in the early 20s and mid-50s, and in both sexes in the late 70s, with 25% of all patients aged 75 or older. A fall was the most frequent cause of TBI, followed by traffic accidents (especially bicyclists). The number of head CT scans increased, and the number of conventional X-rays of the skull decreased compared with 2000/2001. Besides, more patients were offered rehabilitation than before. Though most TBI were classified as mild, one-third of the patients participating in the telephone interview after 12 months still reported troubles attributed to TBI. Negative predictors in mild TBI were female gender, intracranial bleeding and Glasgow Coma Scale (GCS) 13/14. Conclusion: The observed epidemiologic shift in TBI (ie, elderly patients, more falls, more bicyclists) calls for targeted preventive measures. The heterogeneity behind the diagnosis 'mild TBI' emphasises the need for defining subgroups not only based on GCS.